Revolusi Sains dalam Kosmologi dan Implikasinya Terhadap Peradaban: The Scientific Revolution in Cosmology and Its Implications for Civilization - Zulva, Rahmi; Firman, Firman; Nahadi, Nahadi (Undiksha, 2024)
The universe is not only the main topic in cosmology. It acts as a factor that influences the development of paradigms. Circular changes in cosmology will trigger shifts in mindset and civilization development. This circularity of progress is found in the history of human development. The research method in this paper uses a literature review of previous articles on cosmology. This paper attempts to trace these developments in a descriptive-exploratory manner. It is found that the scientific and technological progress of the current generation is affected by the Cartesian-Newtonian cosmological theory. Although it has achieved tremendous success, modern cosmology is still positivistic and has internal flaws. This can be evidenced by the criticisms arising from the same disciplines, although there are different sources from traditional cosmology. Then the change in cosmology also has an impact on other aspects of human existence, the main one being religion. These changes require that a belief is not dependent on a pattern of teaching relying on sacred texts, taking into consideration other elements previously ignored.